Career Success and Personal Failure: Alienation in Professionals and Managers - Korman, Abraham K.; Wittig‐Berman, Ursula; Lang, Dorothy (Academy of Management Journal, 1981)
Expectancy disconfirmation, contradictory role demands, sense of external control, loss of affiliative satisfactions, and developmental life changes are proposed as significant factors in the personal and social alienation among professionals and managers. The research findings generally support the proposed framework.